Neoadjuvant chemotherapy versus surgery alone in locally advanced esophageal squamous cell carcinoma: a propensity-matched real-world study - Wang, Yuchen; Yue, Zhifeng; Li, Zhifeng; Yang, Jin; Yao, Jifang; Liu, Junfeng (Frontiers in Oncology, 2025)
BackgroundThe therapeutic value of neoadjuvant chemotherapy (NAC) for locally advanced esophageal squamous cell carcinoma (ESCC) remains uncertain compared to surgery alone (SA), particularly in real-world settings. This study utilized propensity score matching (PSM) to compare survival outcomes between NAC and surgery in a well-balanced ESCC cohort, while assessing pathological complete response (pCR) and prognostic factors to guide clinical decision-making.MethodsThe study conducted a retrospective analysis of 690 patients with locally advanced ESCC (T3-4aN0-3M0) who underwent radical esophagectomy between 2009 and 2019. PSM was employed to balance baseline characteristics, yielding 452 matched patients (135 NAC, 317 SA). NAC consisted of platinum-based doublet regimens. Survival outcomes, including disease-free survival (DFS) and overall survival (OS), were analyzed using Kaplan-Meier and Cox regression methods. pCR were assessed using CAP criteria.ResultsNAC significantly improved 5-year DFS (28.7% vs. 18.5%, P = 0.001) and OS (37.9% vs. 24.2%, P = 0.001) compared to SA. Patients achieving pCR (11.9%) exhibited superior DFS (5-year: 55.0% vs. 18.5%, P = 0.010) and OS (5-year: 59.8% vs. 35.0%, P = 0.019). Multivariate analysis identified NAC, histologic grade, ypN stage, vessel/nerve invasion, and pCR as independent prognostic factors.ConclusionsThis real-world data supports that NAC significantly improves survival outcomes compared to SA in locally advanced ESCC. pCR post-NAC independently predicted improved OS.